Correlation Between In Vivo Reflectance Confocal Microscopy and Horizontal Histopathology in Skin Cancer: A Review - Broggi, Giuseppe; Verzì, Anna Elisa; Caltabiano, Rosario; Micali, Giuseppe; Lacarrubba, Francesco (Frontiers in Oncology, 2021)
In dermatopathological daily practice, vertical histopathology sections are classically used to analyze skin biopsies. Conversely, horizontal histopathological sections are currently used for the diagnosis of some types of alopecia. In the last years the morphological findings obtained by horizontal histopathology have been correlated to those obtained by in vivo reflectance confocal microscopy which provides the same “point of view” of the skin. This review paper emphasizes the strong matching and correlation between reflectance confocal microscopy images and horizontal histopathology in cutaneous neoplasms, further demonstrating the strong reliability of this innovative, non-invasive technique in the management of skin tumors.